Ancestral grass karyotype reconstruction unravels new mechanisms of genome shuffling as a source of plant evolution - Murat, Florent; Xu, Jian-Hong; Tannier, Eric; Abrouk, Michael; Guilhot, Nicolas; Pont, Caroline; Messing, Joachim; Salse, Jérôme (Genome Research, 2010)
The comparison of the chromosome numbers of today's species with common reconstructed paleo-ancestors has led to intense speculation of how chromosomes have been rearranged over time in mammals. However, similar studies in plants with respect to genome evolution as well as molecular mechanisms leading to mosaic synteny blocks have been lacking due to relevant examples of evolutionary zooms from genomic sequences. Such studies require genomes of species that belong to the same family but are diverged to fall into different subfamilies. Our most important crops belong to the family of the grasses, where a number of genomes have now been sequenced. Based on detailed paleogenomics, using inference from n = 5–12 grass ancestral karyotypes (AGKs) in terms of gene content and order, we delineated sequence intervals comprising a complete set of junction break points of orthologous regions from rice, maize, sorghum, and Brachypodium genomes, representing three different subfamilies and different polyploidization events. By focusing on these sequence intervals, we could show that the chromosome number variation/reduction from the n = 12 common paleo-ancestor was driven by nonrandom centric double-strand break repair events. It appeared that the centromeric/telomeric illegitimate recombination between nonhomologous chromosomes led to nested chromosome fusions (NCFs) and synteny break points (SBPs). When intervals comprising NCFs were compared in their structure, we concluded that SBPs (1) were meiotic recombination hotspots, (2) corresponded to high sequence turnover loci through repeat invasion, and (3) might be considered as hotspots of evolutionary novelty that could act as a reservoir for producing adaptive phenotypes.